2013
DOI: 10.1088/0004-637x/766/2/68
|View full text |Cite
|
Sign up to set email alerts
|

G048.66–0.29: Physical State of an Isolated Site of Massive Star Formation

Abstract: We present continuum observations of the infrared dark cloud (IRDC) G48.660.22 (G48) obtained with Herschel, Spitzer, and APEX, in addition to several molecular line observations. The Herschel maps are used to derive temperature and column density maps of G48 using a model based on a modified blackbody. We find that G48 has a relatively simple structure and is relatively isolated; thus this IRDC provides an excellent target to study the collapse and fragmentation of a filamentary structure in the absence of co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 109 publications
2
18
0
Order By: Relevance
“…The observed nonisothermality of dense clouds, derived from Herschel data, was already reported by other authors (e.g., Stutz et al 2010;Peretto et al 2010;Battersby et al 2011;Wilcock et al 2012;Pitann et al 2013). While the Stutz et al (2010) paper was the pilot study for the globule survey presented here, Peretto et al (2010), Battersby et al (2011), Wilcock et al (2012, and Pitann et al (2013) found that the LoS-averaged dust temperatures in IRDCs also systematically drop toward the highest column densities.…”
Section: Comparison With Earlier Observations and Models Of Dense Coressupporting
confidence: 85%
See 1 more Smart Citation
“…The observed nonisothermality of dense clouds, derived from Herschel data, was already reported by other authors (e.g., Stutz et al 2010;Peretto et al 2010;Battersby et al 2011;Wilcock et al 2012;Pitann et al 2013). While the Stutz et al (2010) paper was the pilot study for the globule survey presented here, Peretto et al (2010), Battersby et al (2011), Wilcock et al (2012, and Pitann et al (2013) found that the LoS-averaged dust temperatures in IRDCs also systematically drop toward the highest column densities.…”
Section: Comparison With Earlier Observations and Models Of Dense Coressupporting
confidence: 85%
“…While the Stutz et al (2010) paper was the pilot study for the globule survey presented here, Peretto et al (2010), Battersby et al (2011), Wilcock et al (2012, and Pitann et al (2013) found that the LoS-averaged dust temperatures in IRDCs also systematically drop toward the highest column densities. Wilcock et al (2012, Fig.…”
Section: Comparison With Earlier Observations and Models Of Dense Coresmentioning
confidence: 83%
“…This is done pixel wise using the following expression (Ward-Thompson & Robson 1990;Faimali et al 2012;Pitann et al 2013;Mallick et al 2015),…”
Section: Temperature and Column Density Distributionmentioning
confidence: 99%
“…The Herschel key programme EPoS (Earliest Phases of Star formation, PI: O. Krause) is dedicated to observations of both high-mass star-forming regions (e.g., Beuther et al 2010Beuther et al , 2013Henning et al 2010;Linz et al 2010;Ragan et al 2012;Pitann et al 2013;Kainulainen et al 2013) and isolated low-mass pre-and protostellar cores (e.g., Stutz et al 2010;Nielbock et al 2012;Launhardt et al 2013;Lippok et al 2013). The focus for the low-mass part of the project is mainly on deriving the density and dust temperature structure in the early phases of protostellar evolution and on determining the initial conditions of protostellar collapse.…”
Section: Introductionmentioning
confidence: 99%